Emerging Trends in Peripheral Artery Disease: A Review of Recent Studies: A Literature Review - Zelda Rizkylia Meidinar Ardis; Agastya, Wayan Dhea (Journal of Diverse Medical Research : Medicosphere, 2024)
Abstract Background. Peripheral artery disease (PAD) is a chronic vascular condition characterized by the narrowing or blockage of peripheral arteries, primarily affecting the lower extremities. It is a major manifestation of atherosclerosis and a significant contributor to cardiovascular morbidity and mortality worldwide. The disease disproportionately affects older adults, smokers, individuals with diabetes, and those with a history of hypertension or hyperlipidemia. Methods. Existing scholarly work was explored through PubMed, Google Scholar, and Scopus, using relevant keywords, such as "peripheral artery disease," "diabetes," "atherosclerosis,” and “short-chain fatty acids.” Discussion. The global burden of PAD has risen, driven by aging populations and increasing prevalence of risk factors. Advances in diagnostic techniques, medical therapies, and interventional approaches have expanded treatment options, but challenges persist in ensuring early detection, equitable access, and effective long-term management. This review aims to synthesize the latest literature on PAD, emphasizing recent developments and identifying gaps that warrant further exploration. Conclusion. The objective of this review is to synthesize recent advancements in our understanding, diagnosis and management of peripheral artery disease (PAD). Peripheral Arterial Disease is a chronic, progressive vascular disorder with significant global health implications. The paper examines the complex relationship between PAD and type 2 diabetes mellitus (T2DM), a prevalent comorbidity linked to increased disease severity and unfavorable outcomes due to shared pathological mechanisms such as endothelial dysfunction, chronic inflammation, and atherosclerosis. Furthermore, it explores emerging treatment strategies, including novel pharmacological agents and innovative therapeutic technologies aimed at enhancing perfusion and mitigating disease progression. Keywords: Peripheral artery disease, diabetes, atherosclerosis, endovascular treatment, short-chain fatty acids, glucose control